Contribution of phenomenology in identifying stressors in youth and adult (Research, Society and Development, 2020)
The school is a space for social reception, mediated by the heterogeneous experiences of its stakeholders, but experiencing the phenomenon of resuming studies after leaving it for a certain time impacts on the biopsychosocial health of these students. This research aims to identify stressors and describe the student's perception of Youth and Adult Education in the context of school dropout. Phenomenological qualitative study, conducted with 25 participants in accordance with CNS Resolution nº 466/2012, approved by the Ethics Committee of the Fluminense Federal University Medical School (CEP FM/UFF), under opinion number 3.333.240. They unveiled two categories of meaning: Body speaks for itself: early pregnancy and lived and not chosen world: decision making: Overwork and Early insertion in the labor market. By these facts it is clear that welcoming is an act of great relevance, considering in its entirety the historical context of the human being. Thus, humanizing, valuing the different subjects implies the process of health production and quality education.